PENGARUH EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI, PEMANFAATAN DAN KESESUAIAN TUGAS DENGAN TEKNOLOGI INFORMASI TERHADAP KINERJA KARYAWAN - Puji Astuti, Ni Made Marlita; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2014)
Sustainability and success of the organization can be determined from the performance of the employee owned. It is expected that employees are able to complete the task and produce information in a timely, accurate, and reliable. This study was conducted to determine the effect of the effectiveness of the implementation of accounting information systems, information technology utilization and appropriateness of tasks with information technology on employee performance. The research was conducted on Credit Unions in Gianyar regency. Samples were taken by purposive sampling technique 40 Credit Unions. Respondents in this study is the chairman or manager, treasurer and cashier. Using multiple linear regression analysis. The results showed the effectiveness of the implementation of accounting information systems, and the suitability of the use of information technology tasks has a positive and significant influence on employee performance.
Keywords: effective implementation of accounting information systems, information technology utilization, suitability to the task of information technology and employee performance